Parental social class and school GCSE outcomes: two decades of evidence from UK household panel surveys. Issue 3 (27th May 2021) - Stopforth, Sarah; Gayle, Vernon; Boeren, Ellen
ABSTRACT: This paper investigates social class inequalities in English school qualifications. The analytical focus is pupils' outcomes in General Certificates of Secondary Education (GCSEs). The original aspect of this paper is the operationalisation of data from the British Household Panel Survey (BHPS) and the UK Household Longitudinal Study (UKHLS), which facilitates analyses from 1991 to 2013. We observe a general trend of improved educational outcomes in more recent cohorts of school pupils, which is consistent with national results. The central empirical finding is that there is a persistent social class gradient. Pupils growing up in families in less advantaged social classes have less favourable school GCSE outcomes. This is especially concerning, because having fewer good GCSEs is likely to limit children's participation in more advanced education and restrict their options in the labour market. Changes in the structure and content of GCSEs lead us to conjecture that sociological analyses of social class inequalities in school qualifications will continue to be important. We highlight the limitations of using administrative educational data, and we outline the data resources that would better facilitate the study of social class inequalities.